THE CULMINATION OF THE SUFISTIC JOURNEY IN A METHODOLOGICAL PERSPECTIVE - Yuniarti, Desi (Archipelago Journal of Southeast Asia Islamic Studies, 2023)
This study discusses the sufistic peak journey. It is so called because the problem of sufism in the plurality of Islamic teachings in the time of the Prophet did not exist. However, the question of sufism is a matter of human beings. The problem of problematic, diacletic and humanist Muslims concerned the ethos of view and its implications for insight into God. Of course, what is talked about in this study is those who go to the sympathic peak so as to find to the peak of happiness in themselves. The focus in this study is how to understand the physical journey? And how does analysis reach a sufistic peak with a methodological approach?. The method used in this research is a type of literature research with a historical approach. The result of this study is to draw closer as possible to God, so that it can be seen with the eyes of the heart that even one's spirit can unite with the Spirit of God. The method one takes to get to the peaks of sufistic achievement, is so long and tortuous. Even the circumstances experienced when he reached the top were very varied and varied.